Enhancing maize drought and heat tolerance: single vs combined plant growth promoting rhizobacterial inoculation - Notununu, Iviwe; Moleleki, Lucy; Roopnarain, Ashira; Adeleke, Rasheed (Frontiers in Plant Science, 2024)
Maize (Zea mays L.), a key staple crop in Sub-Saharan Africa, is particularly vulnerable to concurrent drought and heat stress, which threatens crop yield and food security. Plant growth-promoting rhizobacteria (PGPR) have shown potential as biofertilizers to enhance plant resilience under such abiotic stresses. This study aimed to (1) identify PGPR isolates tolerant to drought and heat, (2) assess their capacity to mitigate the effects of these stresses on early maize growth, and (3) analyze maize gene expression changes associated with PGPR-induced tolerance. Rhizobacteria were isolated and screened for drought and heat tolerance, alongside key plant growth-promoting (PGP) traits, including phosphorus solubilization, nitrogen fixation, and indole acetic acid production. In vitro and pot trials evaluated the effects of selected isolates on maize growth under stress, using indicators such as shoot length, root and shoot biomass (wet and dry), and leaf water content. Quantitative reverse transcription PCR (qRT-PCR) was employed to profile maize stress response genes. The identified PGPR isolates included Bacillus cereus (11MN1), Bacillus pseudomycoides (21MN1B), Lelliottia amnigena (33MP1), and Leclercia adecarboxylata (36MP8). Greenhouse trials demonstrated that L. amnigena 33MP1, L. adecarboxylata 36MP8, and a mixed culture of isolates (11MN1, 21MN1B, 33MP1, 36MP8) effectively alleviated the adverse effects of concurrent drought and heat stress in maize. Notably, qRT-PCR analysis indicated that PGPR-induced tolerance may involve the modulation of stress response genes CAT2 (catalase 2) and DHN2 (dehydrin 2), which play roles in oxidative stress management and cellular protection. The PGPR isolates identified in this study represent promising bioinoculants for enhancing maize resilience under climate-induced stresses, offering a sustainable approach to improve maize productivity, conserve water, and reduce irrigation needs in drought-prone regions.